Subcritical water pretreatment for anaerobic digestion enhancement: a review - Aili Hamzah, Adila Fazliyana; Hamzah, Muhammad Hazwan; Che Man, Hasfalina; Jamali, Nur Syakina; Siajam, Shamsul Izhar; Show, Pau Loke (Universiti Putra Malaysia Press, 2023)
This work reviews hydrothermal subcritical water pretreatment to enhance biogas production through anaerobic digestion. The complexity of the lignocellulosic structure has been the main limitation contributing to unsatisfactory biogas production throughout the anaerobic digestion. The high resistance of the structure to biological hydrolysis has increased the interest in applying pretreatment prior to anaerobic digestion to facilitate hydrolysis. Hydrothermal subcritical water technology, an environmentally friendly pretreatment that uses water as the main medium, is gaining prominence in biogas enhancement. However, the subcritical water pretreatment influence on structural properties, biogas production, and the production of anaerobic process inhibitors signifies a knowledge gap and needs an evaluation. This review presents the need for pretreatment reaction and properties in the subcritical water region, biogas production from subcritical water pre-treated waste, production of inhibitors, and its challenges are discussed. This pretreatment could be a promising option and further enhance biogas production throughout the anaerobic digestion process.